Introducing the PrimeD Framework: Teacher Practice and Professional Development through Shulman's View of Professionalism - Jon Saderholm; Robert N. Ronau; Christopher R. Rakes; Sarah B. Bush; Margaret J. Mohr-Schroeder (MDPI AG, 2024)
This paper clarifies and expands the definition of teacher professional practice, grounded in the commonplaces of professionalism outlined by Lee Shulman. We present the Professional Development: Research, Implementation, and Evaluation (PrimeD) framework as a lens for transforming professional development into a practice that engages teachers as professionals. This discussion explores teachers' roles in both their classrooms and the profession. The inclusion of PrimeD evaluation and research in the development and practice of mathematics teachers addresses Shulman's professionalism commonplaces. PrimeD was tested as a lens for professionalism in mathematics teacher education programs at four universities. In the study, teachers collaborated as professionals on developing and testing novel ways to approach mathematics lessons. In general, teachers' efforts to conduct structured experimentation in their lessons were disconnected from traditional views of the role of a teacher. As a result, teachers who did develop and test lesson trials in this PD program did not frequently continue experimentation. Typically, teachers wanted to collaborate on testing classroom activities but did not have resources to do so (e.g., time, collaborative planning). Systemic changes are needed to promote sustainable change, allowing teachers to collaborate and share the results of classroom research.